(untitled) (International Journal of Built Environment and Sustainability, 2023)
Natural resources are increasingly under pressures to cater for the growing human population and their corresponding, often conflicting needs. However, the need to conservatively utilize these resources without deteriorating the environment to the disadvantage of the future generations has prompted some actionable steps at the global level, the prominent of which is the promulgation of the United Nation’s Sustainable Development Goal 2030 (SDG-2030) Agenda, having seventeen (17) inter-related actionable areas of human endeavours (i.e., Agenda). Of particular interest within this context is the Agenda Thirteen (Agenda-13) which encompasses the need for urgent action to combat Climate Change and its impacts across various areas of human engagements. This is necessary as Climate Change impacts are characterized with anthropogenic carbon emissions resulting in global temperature rise, sea level rise, flooding, desertification, droughts, and other related disasters. Within the precinct of Built Environment, it is established that building construction and operation alone account for about 40% of the global emissions. This calls for concerns and requires urgent collaborative actions to curtail the trend. This submission, which is review based therefore, highlights various joint efforts particularly, integration of technological advancements by the relevant building professionals, towards attaining the goal of Agenda-13. This is with a view to limiting climate change enablers for reduced environmental impacts. These collaborative efforts are categorized into pre-construction and post-construction activities from the relevant professionals in the built environment. While the former includes Indoor Thermal Comfort Simulation, Integration of Daylighting Technologies, and adoption of Computational Fluid Dynamics integrated architectural design process, the latter consists of design of Double Skin Facades, development of Building Integrated Photovoltaics façade, integration of Evacuated Tube Solar Air Collector System, adoption of Phase Change Material on Building façade, and implementation of Life Cycle Energy Analysis Policy, among others. These endeavours aim at reducing carbon emissions at the building micro level for overall clean, safe and sustainable global environment.